Impacts of an introduced marine invertebrate on wintering shorebirds - Estelle, Veronica B., author; Noon, Barry R., advisor; Savidge, Julie A., advisor; Grosholz, Edwin D., committee member; Wiens, John A., committee member (Colorado State University. Libraries, 2006)
It has been speculated that the introduction of the European green crab (Carcinus maenas) along the West Coast of North American may pose a threat to migratory and wintering shorebirds that use similar habitats and prey resources. I conducted a literature review to determine the current state of knowledge on the effects of marine introduced species on shorebirds. I explored potential impacts of green crabs on Dunlin (Calidris alpina) prey consumption, foraging behavior, and weight change in Bodega Harbor and Bolinas Lagoon, CA. To do this I used a randomized complete block experiment in which green crab density was the treatment. I further explored potential impacts of green crabs on Dunlin through an observational study of Dunlin diets in these two embayments after the green crab introduction. I compared data on Dunlin diets prior to the arrival of green crabs in these locations with current diet data to assess whether Dunlin diets have changed since the green crab's introduction. In Chapter 1, I reviewed the literature to assess effects of introduced species (marine plant or animal) on shorebirds. The body of literature addressing this topic is fairly sparse. I found 12 references in which effects of introduced marine organisms on shorebirds are considered; 6 studies considered introduced marine invertebrates and 6 introduced plants. The plant studies were by far the more rigorous, and investigated the question of impact of the introduced species upon shorebirds. Most of these studies took place in England; there is no published research from North America regarding the effects of introduced marine plants on shorebirds. The primary plant effects were related to loss of habitat and changes in invertebrate prey communities within patches of Spartina alterniflora (and its various hybrids) and Zostera maritima. Authors specifically discussed the impact and implications of these plant invasions on shorebirds. In contrast, studies on introduced invertebrates in marine environments were more speculative about impacts and implications for shorebirds, and there were no examples of manipulative experiments to investigate causal relationships between these organisms. Of the invertebrate studies conducted, one showed no effect on shorebird abundance and distribution in one embayment in North America, and another showed increased reproductive output of the Black Oystercatcher (Haematopus moquini) in one location (South Africa). Because estuaries are among the most heavily and rapidly invaded coastal ecosystems and because shorebirds rely upon the food and habitat resources of these systems, there is a need to evaluate the ecological effects of these novel species on shorebirds. I hypothesize that the primary effects of introduced marine plants and animals will be mediated through space and food resources and will involve indirect effects. In Chapter 2, I used a manipulative field experiment to examine shorebird responses to the effects of green crab predation on invertebrate prey. I set up a randomized complete block design with green crab density as the treatment. The experiment was conducted in two parts, a crab foraging experiment, followed by a Dunlin foraging experiment. I expected that temporal, spatial, and environmental variation in prey density could affect my ability to detect changes in this response variable, and so I incorporated specific experimental design features (Before After Impact Control, blocking, and paired sampling) to minimize variation from these sources. I found that green crabs significantly reduced the prey density of a crustacean species, but not of other prey taxa that it previously affected (esp. the clam Nutricola spp.). This result was contrary to other studies, and may be related to past effects of green crab predation and to unusually low prey density during the season in which the experiment was conducted. I also found that Dunlin were able to reduce the density of a polychaete in areas where no green crabs had foraged compared to areas where high densities of green crabs had been held. Additionally, Dunlin reduced the density of Nutricola spp. in cages where high densities of green crabs were held compared to zero density cages. This result was also contrary to results of previous studies, and it may be related to indirect effects of holding green crabs in a cage at high density or to some other aspect of their foraging behavior. If this treatment effect holds beyond the experimental conditions, this would provide another mechanism by which the green crab negatively impacts Nutricola spp. I detected no effects of green crabs on Dunlin foraging behaviors or weight. However, both Dunlin and green crab diet were different from free-ranging individuals in that fewer Dunlin consumed clams in the experiment than in non-captive conditions, and green crabs foraged on gastropods, not clams, during the experiment. Experimental results combine to suggest that prey conditions (density) affected green crab predation, and this in turn, affected Dunlin prey consumption and dietary composition. Further implications of this research will need to be evaluated in an energetics context, and with attention to shorebird body condition and winter survival rates as these may affect population parameters. As marine invertebrate communities continue to change with the introduction of marine organisms, it will become important to the management and conservation of shorebirds to consider the ecological role of introduced marine plants and animals, particularly in locations where large numbers of shorebirds congregate during migration or winter. In Chapter 3, I conclude with an examination of Dunlin diet in Bolinas Lagoon and Bodega Harbor, CA. I compared Dunlin diet prior to the green crab's introduction with that after the crab's arrival to assess whether any changes had occurred in Dunlin diet during this time, with the understanding that any documented changes do not necessarily imply a causative relationship. Dunlin diet remains highly variable between locations and among years, and all major prey taxa (molluscs, crustaceans, polychaetes and insects) occur presently in their diets. However, when results from previous studies on changes in invertebrate density and size are considered, it is clear that the bivalve component (esp. Nutricola spp.) of the Dunlin diet in Bodega Harbor is currently comprised of fewer, smaller individuals than previous to the introduction of the crab. The present diet of Dunlin in Bodega Harbor appears more similar to that in Bolinas Lagoon than it did historically, but number of annual samples is too minimal during each period to be supportive of a causative relationship. Prior to introduction of the green crab in Bolinas Lagoon, the primary prey of Dunlin was polychaetes and crustaceans, not bivalves. Currently in Bolinas Lagoon, the Dunlin diet has a significantly higher percent occurrence of bivalves and a lower percent occurrence of crustaceans than it did prior to the green crab's arrival. In this location, Dunlin may now forage upon smaller individual bivalves, particularly Nutricola spp. than before the crab's introduction. There may be energetic costs to these dietary changes, and these should be examined with regard to effects on shorebird winter body condition and survival rates. I conclude that future research on change in shorebird populations, diets, and foraging should consider changes in invertebrate biota due to introduced marine invertebrates. In the future, shorebird diet should be examined as a function of relative abundance of native vs. non-native prey composition.
Keywords: zoology; ecology; oceanography; biological oceanography